Manufacture of Solid Polymer Electrolyte (SPE) Based on PVDF HFP-LiBOB - Humaidi, Syahrul; Aldira, Syarah; Lestariningsih, Titik (Talenta Publisher, 2022)
This research aimed to synthesize solid polymer electrolyte (SPE) with and without Polyethylene oxide (PEO) using the solution cast technique. The liquid electrolyte of LiBOB was synthesized with the immersing method. The chemicals used are PVDF-HFP (0.75 g), TiO2(0.05 g), PEO(0.25 g), DMAC, EC, EMC, and LiBOB(1.55 g). The morphology of the surface membrane was characterized using SEM. The results of the SEM analysis shows that the addition of PEO plays a role in forming the SPE membrane because the addition of PEO greatly affects the density of the SPE sheet.